2021
DOI: 10.7454/jki.v24i2.990
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Spiritual Intervention in Overcoming Anxiety and Depression Problems in Gynecological Cancer Patients

Abstract: Anxiety and depression are psychological distress that often occurs in gynecological cancer patients. However, there are few studies related to interventions to overcome these problems. The purpose of this study was to determine the effect of a spiritual intervention on anxiety and depression in such cancer patients. The research design was quasi-experimental, employing pretest and posttest on the intervention and the control groups. The total number of respondents was 108 patients, consisting of 54 in each gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
1
0
3
Order By: Relevance
“…The research of Sleight et al, showed that spiritual peace and life meaning may buffer the effect of anxiety on physical well-being in newly diagnosed cancer survivors (34). Findings of Nasution et al, indicate the effect of spiritual intervention in overcoming anxiety problems in gynecological cancer patients (35). The findings of Basharpoor et al show positive group psychotherapy increases self-differentiation and reduces the death anxiety in women with breast cancer (36).…”
Section: Discussionmentioning
confidence: 99%
“…The research of Sleight et al, showed that spiritual peace and life meaning may buffer the effect of anxiety on physical well-being in newly diagnosed cancer survivors (34). Findings of Nasution et al, indicate the effect of spiritual intervention in overcoming anxiety problems in gynecological cancer patients (35). The findings of Basharpoor et al show positive group psychotherapy increases self-differentiation and reduces the death anxiety in women with breast cancer (36).…”
Section: Discussionmentioning
confidence: 99%
“…Kanker telah dilaporkan menjadi penyakit kronis yang mempunyai dampak yang cukup besar dalam fisik, emosional, sosial dan kesehatan spiritual Kanker ginekologi menjadi salah satu penyebab kesakitan dan kematian wanita di negara berkembang Diagnosis kanker menyebabkan penderitaan dan kecemasan bagi individu beserta keluarga penderita kanker [2]. Penderita kanker akan mengalami berbagai gejala fisik dan psikologis dalam proses penyakitnya diantaranya adalah nyeri, kelelahan, perubahan fisik lainnya [3] sedangkan bentuk gangguan psikologis yang dialami pasien kanker ginekologi yang biasa terjadi adalah kecemasan dan depresi [4] yang akan berdampak pada mekanisme koping dan menggangu kesejahteraan spiritualnya [5]. Pasien dengan kanker dengan gejala nyeri berat lebih bergantung pada bantuan orang lain serta kebutuhan spiritualnya jauh lebih tinggi daripada penderita kanker yang mempunyai gejala yang lebih ringan [6].…”
Section: Latar Belakangunclassified
“…Berdoa adalah kebutuhan spiritual dan mengajarkan tekanan spiritual. Berdoa merupakan perilaku individu yang juga dapat mempengaruhi kepuasan diri dan dukungan social (Nasution et al, 2021). Berdoa sering dikaitkan dengan keyakinan seseorang, Tidak ada perbedaan dalam jenis terapi CAM yang digunakan dengan tingkat keimanan seseorang (Almasdy et al, 2018).…”
Section: Pembahasanunclassified